Bashkirian Rugosa (Anthozoa) from the Donets Basin (Ukraine). Part 7. The Family Neokoninckophyllidae Fomichev, 1953, with a preliminary revision of Moscovian taxa - Fedorowski, Jerzy (Acta Geologica Polonica, 2019)
The Family Neokoninckophyllidae and its type genus Neokoninckophyllum Fomichev, 1939 (type species: N. tanaicum Fomichev, 1939) are discussed and emended. In addition, the genera Orygmophyllum Fomichev, 1953 and Yuanophylloides Fomichev, 1953, originally included in the Families Campophyllidae Wedekind, 1922 and Lophophyllidae Grabau, 1928, respectively, are emended as well and transferred to the Neokoninckophyllidae. Two early Bashkirian species, viz. Yuanophylloides rectus (Vassilyuk in Aizenverg et al., 1983) and Y. inauditus (Moore and Jeffords, 1945), and the Moscovian Neokoninckophyllum sp. nov. are described on the basis of new collections from the Donets Basin. Neokoninckophyllum tanaicum, Yuanophylloides gorskyi Fomichev, 1953 (both Moscovian in age) and Y. cruciformis Fomichev, 1953 (latest Bashkirian), are redescribed on the basis of peels taken from Fomichev’s (1953) type specimens. Derivation of the Family Neokoninckophyllidae from the Subfamily Dibunophyllinae Wang, 1950 is postulated and phylogenetic links within the former are hinted at. The occurrence of Yuanophylloides inauditus in both the Donets Basin and the Western Interior Province of North America points to marine communication between those areas during the Bashkirian. The slightly earlier appearance of the oldest neokoninckophyllids in the Donets Basin, in comparison to North America (i.e., R1 vs R2 ammonoid biozones), documents the common roots and monophyletic development of the Neokoninckophyllidae in both areas.
Keywords: Carboniferous (Pennsylvanian); Neokoninckophyllidae; Emendation; Phylogeny; Palaeogeographic implications